SAT0006 No Differences in Patient-Reported Outcomes by Methotrexate Dose Among Early Rheumatoid Arthritis Patients Treated Concomitantly with Adalimumab: Results from the Concerto Trial. (23rd January 2014) - Fleischmann, R. M.; Kivitz, A.; van Vollenhoven, R. F.; Shaw, J. W.; Florentinus, S.; Karunaratne, M.; Kupper, H.; Dougados, M.; Burmester, G.-R.
Abstract : Background: Methotrexate (MTX) in combination with the tumor necrosis factor inhibitor adalimumab (ADA) is an effective therapy for treating rheumatoid arthritis (RA), but the minimum dose of MTX in combination with ADA that can achieve an acceptable clinical response is not known. Objectives: To evaluate different MTX doses in combination with ADA in achieving clinically meaningful improvement in patient-reported outcomes (PROs) in patients (pts) with early RA. Methods: CONCERTO was a 26-week (wk), phase 3, double-blind, parallel-arm study in MTX-naïve pts with active RA <1 year in duration. Pts were randomized 1:1:1:1 to open-label ADA 40 mg every other wk plus blinded weekly oral MTX in a dose of 2.5, 5, 10, or 20 mg. Pts in the 20 mg arm started with 10 mg MTX with bi-weekly escalation of 2.5 mg through wk 8. PROs measured at wks 8 and 26 included the following: Health Assessment Questionnaire Disability Index (HAQ-DI); patient global assessment of disease activity (PGA); 36-item Short-Form Health Survey, Version 2 (SF-36v2) Physical Component Summary (PCS) and Mental Component Summary (MCS); Medical Outcomes Study Sleep Scale (MOS SS); Compliance Questionnaire Rheumatology (CQR); and Treatment Satisfaction Questionnaire for Medication (TSQM). Differences in mean changes in PROs among the 4 treatment groups were analyzed using mixed models. No adjustments for multiplicity were applied. Results: Of the 395 pts included in the intent-to-treat population, 358 (91%) completed 26 wks of treatment; 15, 7, 6, and 9% of pts receiving 2.5, 5, 10, or 20 mg MTX, respectively, discontinued treatment prior to completion. Clinically and statistically significant improvements from wk 0 in most PROs occurred in all 4 dose groups by 8 wks, were maintained through 26 wks, and were similar regardless of MTX dose with no statistically significant difference between the dose groups with respect to the HAQ-DI, PCS, and MCS. Image/graph: Conclusions: Pts treated with ADA in combination with MTX 2.5, 5, 10 or 20 mg per wk experience similar improvements in PROs by wk 8 that are maintained through 26 wks. The differences associated with MTX dose are not statistically significant and, in general, not clinically meaningful. Acknowledgements: AbbVie Inc. funded the study (NCT01185301 ). AbbVie was responsible for the study design, research, analysis, data collection, interpretation of data, and writing, reviewing, and approving of the publication. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, and Douglas E. Dylla, PhD., of AbbVie. Disclosure of Interest: R. Fleischmann Grant/research support from: AbbVie, Pfizer, Merck, Roche, UCB, Celgene, Amgen, Astra-Zeneca, BMS, Janssen, Lilly, and Novartis., Consultant for: AbbVie, Pfizer, Merck, Roche, UCB, Celgene, Amgen, Astra-Zeneca, BMS, Janssen, Lilly, and Novartis., A. Kivitz Grant/research support from: AbbVie, Amgen, AstraZeneca, BMS, Celgene, Genentech, Janssen, Pfizer, and UCB, Consultant for: BMS, Genentech, and UCB, Speakers bureau: BMS, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, Human Genome Sciences, Merck, Pfizer, Roche, and UCB, Consultant for: AbbVie, BMS, GSK, Human Genome Sciences, Merck, Pfizer, Roche, and UCB, J. Shaw Shareholder of: AbbVie, Employee of: AbbVie, S. Florentinus Shareholder of: AbbVie, Employee of: AbbVie, M. Karunaratne Shareholder of: AbbVie, Employee of: AbbVie, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie, M. Dougados Grant/research support from: AbbVie, BMS, Merck, Novartis, Pfizer, Sanofi-Aventis, and UCB., Consultant for: AbbVie, BMS, Merck, Novartis, Pfizer, Sanofi-Aventis, and UCB., G.-R. Burmester Grant/research support from: AbbVie, Essex/Schering-Plough, Novartis, Roche, and Wyeth., Consultant for: AbbVie, Essex/Schering-Plough, Novartis, Roche, and Wyeth., Speakers bureau: AbbVie, Essex/Schering-Plough, Novartis, Roche, and Wyeth.